Pengaruh Lingkungan Kerja dan Motivasi Kerja terhadap Kinerja Karyawan pada PT. Pos Indonesia Aceh Barat - Nurhanisah; Chairiyaton (Regress: Journal of Economics & Management, 2023)
This article aims to discuss the influence of the work environment and work motivation on employee performance at PT Pos Indonesia Aceh Barat. PT Pos Indonesia Aceh Barat is a state-owned enterprise business that is engaged in sending packages, documents and goods to various areas of West Aceh. In carrying out its activities, employee performance needs to be improved in order to increase the consistency of the company so that it can evaluate and change in an increasingly advanced era. The purpose of this study intends to determine and determine the influence of environmental factors and work motivation obtained by employees on the performance of PT Pos Indonesia Aceh Barat employees. The data collection technique was carried out by distributing questionnaires (questions) to employees and then analyzed using multiple linear regression tests through the SPSS version 25 tool. The results showed that environmental variables and work motivation at PT Pos Indonesia Aceh Barat were able to have a positive impact and had an impact significantly to employee performance by 87.2%.